Banking crises and business cycle: evidence for Italy(1861-2016). Issue 1 (26th October 2018) - Bartoletto, Silvana; Chiarini, Bruno; Marzano, Elisabetta; Piselli, Paolo
Abstract : Purpose: This paper aims to focus on the banking crises recorded in Italy in the period 1861-2016 and to propose a novel classification based upon the timing of the crisis with respect to the business cycle. Design/methodology/approach: A simple and objective rule to distinguish between slowdown and inner-banking crises is introduced. The real impact of banking crises is evaluated by integrating the narrative approach with an empirical vector autoregression analysis. Findings: First, banking crises are not always associated to economic downturns. Especially in Italy, (but this analysis can be easily extended to other countries), they have often limited their negative effects within the financial system ("inner" crises). Second, the simultaneity of macroeconomic effects (credit contraction and GDP recession) leave the causal link undetermined. Third, the empirical and narrative analyses performed testify that boom–bust mechanisms are an exception in the panorama of (Italian) banking crises; although when the economy experiences such episodes, the economic and social consequences are not only severe but also enduring. Research limitations/implications: To classify historically recognized banking crisis episodes, the authors look at credit and GDP dynamics (and their ratio) around crisis years. Relying on a single definition of crisis is avoided. The classification provides an empirical rule to determine in what way banking crises differ. The classification is mostly based on the synchronization with the business cycle and, using the documented evolution of macroeconomic aggregates, it permits to highlight the fact that a variety of interactions occur between financial and real aggregates during and around banking crises. Originality/value: As to the concept of systemic banking crisis, a qualitative judgment is often adopted to select relevant episodes, thus confirming the absence of a quantitative rule in classification criteria (Chaudron and de Haan, 2014 ). This paper proposes a simple and objective rule to distinguish between slowdown and inner-banking crises; the former occur close to a GDP contraction, whereas the latter appear to spread their effects with no substantial evidence of output loss.